EFFICACY OF EGG PARASITOID (TRICHOGRAMMA CHILONIS ISHII) AND PUPAL PARASITOIDS (NESOLYNX THYMUS GIRAULT AND TETRASTICHUS HOWARDII OLIFF) AGAINST DIAPHANIA PULVERULENTALIS (HAMPSON) (LEPIDOPTERA : PYRALIDAE), A PEST OF MULBERRY - NARAYANASWAMY, K.C.; JAGADISH, K.S.; BABU, S. HARISH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2016)
The parasitization potential of egg parasitoid, Trichogramma chillonis Ishii and two pupal parasitoids, Tetrastichus howardii Oliff and Nesolynx thymus Girault were evaluated against Diaphania pulverulentalis (Hampson) under laboratory conditions. The exposure of one, two and three day old eggs of D. pulverulentalis to adults of T chillonis resulted in parasitization rate of 90.84+ 1.18, 90.00+0.00 and 72.50+5.90 per cent, respectively. The pre-pupae and pupae in the age group ranging between one to eight days were exposed to the adults of T. howardii under laboratory conditions and the rates of the pupal parasitization were recorded. The results revealed that at pre-pupal stage, the parasitization was maximum (86.67%), however, it decreased as the age of exposure of pupae to the parasitoid was increased. Thus, maximum rates of parasitization was observed when pupal age at exposure to parasitoid was 1, 2, 3 and 4 days, whereas the parasitoid did not parasitize the pest when 7 and 8 day old pupae were exposed. In case of N. thymus, when pre-pupae were exposed to the parasitoid, the parasitization was 13.33+0.00 per cent. However, pupae exposed to N. thymus at 6, 7 and 8 days of age recorded no parasitization. Among the parasitoids tested, T. chilonis recorded highest parasitization. Between the two pupal parasitoids, T. howardii was superior than N. thymus under laboratory conditions.